Class Discrimination? Evidence from Jamaica: A Racially Homogeneous Labor Market. (March 2020) - Spencer, Nekeisha; Urquhart, Mikhail-Ann; Whitely, Patrice
A common concern in audit studies of racial discrimination is that names assigned to a particular race may also proxy for socioeconomic status. We conduct a correspondence study in Jamaica, a predominantly black middle-income country, and find that these concerns may be valid. The evidence from sending out over 1, 000 résumés suggests employers prefer applicants perceived to be from high-income backgrounds. While qualifications are not independently important, those with names preferred by employers have a lower chance of being selected if they have high-quality résumés. The results suggest that class discrimination may matter as much as race discrimination. JEL Classification: I31, J71, J64